CONTEXTUAL QUR’ANIC INTERPRETATION IN INDONESIA: A HERMENEUTICAL STUDY OF DAWAM RAHARDJO’S ENSIKLOPEDI AL-QUR’AN - Zainuddin, Ahmad; Muin, Abd.; Mohd Fadzli, Ahmad Iqbal; Iffah, Iffah (Universitas Nurul Jadid, 2025)
This study explores the contextualization of Dawam Rahardjo’s Ensiklopedi Al-Qur’an, aiming to examine his paradigm of contextual interpretation and analyze how it is reflected in one of the entries within his work. Employing a qualitative method based on literature review, this research adopts Abdullah Saeed’s theory of contextual interpretation as the hermeneutical framework for engaging with the Qur’an. The study presents two main findings. First, Dawam Rahardjo’s interpretive paradigm is demonstrably contextual. This is evident in his emphasis on the importance of understanding the Qur’an within the context of its revelation. He further argues that the values of the Qur’an must not remain confined to their historical context but should be internalized within contemporary Indonesian society as a foundation for both social and intellectual engagement. Second, Dawam’s contextual approach is reflected in his interpretation of the prohibition of riba (usury). In its revelatory context, the addition of value in lending was condemned because it typically involved oppressive consumer debt, particularly burdening low-income individuals. By contrast, Dawam argues that modern bank interest does not fall under the category of riba, since it involves productive loans and serves as a payment for the services rendered by financial institutions, which are legally regulated. Another example of Dawam’s contextual methodology is his interpretation of the term ummah in QS. Ali Imrān (3): 104. He understands ummah as referring to the concept of a state, linking it to both the historical development of the Madinah Charter and to modern notions of the social contract.